MATERIALS MANAGEMENT: A REVERSE LOGISTICS CASE OF AGROTOXICS EMPTY CONTAINERS IN A SUGAR AND ALCOHOL COMPANY - Pereira Junior, Humberto dos Santos; Cortez, Renan Marcelo; Penedo, Antonio Sergio Torres; Lima, Nilton Cesar; de Souza, Gustavo Henrique Silva; da Silva, Thiago Emidio Esteves; Queiroz, Jamerson Viegas; Martins, Elvis Silveira (European Scientific Journal, ESJ, 2013)
With the advances in today’s chemical pesticides, global agriculture has become extremely productive, which, from another point of view, brought many environmental problems, especially in relation to damage caused by pesticides and the improper disposal of their packages. Brazil, on the other hand, holds the world record in the collection and recycling of empty pesticides containers, which could only be configured within a process of compromise among all stakeholders: from the manufacturers of pesticides to the farmer (or rural enterprise). The objective of this study was to analyze the ﻿measures taken from storage, to transportation, and to collection posts of empty pesticides containers, by a large Brazilian sugar and ethanol company. The methodology has adopted of an exploratory nature within a qualitative approach, through a semi-structured interview with the logistics and material manager of the company investigated. It was found that the company follows a strict process of handling empty containers of pesticides, following the standards and laws of the country, aiming to achieve the ISO14000 certification, for the social compromise to the community in which it operates.